TT deformations of non-relativistic models - Frolov, Sergey; Esper, Chantelle (My University, 2021)
The light-cone gauge approach to TT¯¯¯¯ deformed models is used to derive the TT¯¯¯¯ deformed matrix nonlinear Schrödinger equation, the Landau-Lifshitz equation, and the Gardner equation. Properties of one-soliton solutions of the TT¯¯¯¯ deformed nonlinear Schrödinger and Korteweg-de Vries equations are discussed in detail. The NLS soliton exhibits the recently discussed phenomenon of widening/narrowing width of particles under the TT¯¯¯¯ deformation. However, whether the soliton’s size is increasing or decreasing depends not only on the sign of the deformation parameter but also on soliton and potential parameters. The TT¯¯¯¯ deformed KdV equation admits a one-parameter family of one-soliton solutions in addition to the usual velocity parameter. The extra parameter modifies the properties of the soliton, in particular, it appears in the dispersion relation.
PUBLISHED
Keywords: Integrable Field Theories; Field Theories in Lower Dimensions; Theoretical Physics